Human resource management of Kuehne+Nagel Ltd and recommendations on its improvement - Sajid, Md. Ariful Islam (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Masters of Business Administration, 2018.